Association Between Triglyceride Glucose Index and Hypertension According to Different Diagnostic Criteria - Hao H; Geng H; Ma M (International Journal of General Medicine)
Hua Hao, Hui Geng, Mao Ma Physical Examination Center, the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of ChinaCorrespondence: Mao Ma, Email mamaoxj@163.comObjective: To explore the association between triglyceride glucose index (TyG) and hypertension under different diagnostic thresholds.Methods: This study analyzed data from routine occupational health examinations conducted at the First Affiliated Hospital of Xi’an Jiaotong University in 2019. TyG and TyG-BMI, indicators of insulin resistance (IR), were calculated using triglyceride (TG), fasting blood glucose (FPG), and body mass index (BMI). Hypertension was defined by thresholds of 140/90 mmHg and 130/80 mmHg. Logistic regression models were employed to investigate the association between TyG and hypertension.Results: Among 4028 subjects, after adjusting for covariates, the risk of hypertension (diagnosed by 140/90 mmHg) was 2.87 times higher (OR=2.87, 95% CI: 2.11– 3.91) in the Q4 group of TyG compared to the Q1 group. Similarly, the risk was 8.03 times higher (OR=8.03, 95% CI: 5.05– 12.75) in the Q4 group of TyG-BMI than in the Q1 group. Furthermore, the risk of hypertension (diagnosed by 130/80 mmHg) was 2.93 times higher (OR=2.93, 95% CI: 2.34– 3.68) in the Q4 group of TyG compared to the Q1 group, and 7.12 times higher (OR=7.12, 95% CI: 5.08– 9.99) in the Q4 group of TyG-BMI than in the Q1 group. The restricted cubic spline further showed a dose-response relationship between TyG/ TyG-BMI and hypertension. In the population with a BMI of 24.0– 27.9 kg/m2, the risk of developing hypertension (diagnosed by 140/90 mmHg) in the Q4 group of TyG was 2.79 times higher (OR=2.79, 95% CI: 1.67– 4.66), while the Q4 group with TyG had a 3.07 times greater risk of hypertension (diagnosed by 130/80 mmHg) than the Q1 group (OR=3.07, 95% CI: 2.05– 4.60).Conclusion: TyG is an independent risk factor for hypertension across different thresholds, showing a clear dose-response relationship. BMI may influence this association, emphasizing the importance of managing insulin resistance early to aid hypertension prevention.Keywords: triglyceride glucose index, hypertension, insulin resistance, body mass index